Eleanor Roosevelt - Donnelly, Shannon ([S.l.] : Heinle Cengage Learning, 2007)
Teaches students the life stories of great American heroes while enhancing reading skills. By providing students with this important foundation, this title offers a fresh approach to teaching American culture while expanding fluency.
Keywords: English language -- Sound recordings for foreign speakers; Presidents' spouses -- United States -- Biography